2005
DOI: 10.1093/bja/aei238
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different epidural solutions in off-pump cardiac surgery: pilot study

Abstract: We conclude that immediate extubation after OPCAB using TEA is feasible with different TEA regimens. Respiratory function, haemodynamic stability and pain control are not different between TEA with bupivacaine alone, bupivacaine with fentanyl or bupivacaine with clonidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Concern has been described about the possible effect of clonidine addition in epidural infusions because of the possible effect on the blood pressure. Whereas one recent study [34] showed lower blood pressure when clonidine was added to ropivacaine for epidural analgesia after spinal anesthesia, we could not support these findings in a previous study with the same study setup [35,36] Although this was not the main focus of the study, perioperative blood pressure and heart rate remained stable and was not different between the three groups.…”
Section: Clonidine In Epidural Administrationcontrasting
confidence: 79%
“…Concern has been described about the possible effect of clonidine addition in epidural infusions because of the possible effect on the blood pressure. Whereas one recent study [34] showed lower blood pressure when clonidine was added to ropivacaine for epidural analgesia after spinal anesthesia, we could not support these findings in a previous study with the same study setup [35,36] Although this was not the main focus of the study, perioperative blood pressure and heart rate remained stable and was not different between the three groups.…”
Section: Clonidine In Epidural Administrationcontrasting
confidence: 79%
“…Thoracic epidural analgesia (TEA) with general anesthesia (GA) can provide high-quality analgesia and quick rehabilitation when IE was done with TEA along with GA.[ 2 ] It also ensures hemodynamic stability and allows early extubation. [ 12 ] Nonetheless, it is not essential to obtain optimal results in UFTA,[ 11 ] and the less invasive cardiac anesthesia is promising as well. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Continuous infusion of low concentration of local anaesthetics avoids motor blockade and spare autonomic function to the urinary bladder, carries no significant toxicity and requires minimal attention from the staff in the ward. [8,9,10] Thus Elastomeric pump which represents a technologic advance in late 80s is relatively inexpensive disposable non mechanical pump may be proposed to provide epidural, perineural, direct wound and intra-articular local anaesthetics infusion for post-operative pain relief. [ 11,12 ] The pump had a capacity of 125ml and was designed to deliver drug @ 5ml/hour for 24 hours continuously.…”
Section: Discussionmentioning
confidence: 99%